PENGARUH FASILITAS KERJA TERHADAP KINERJA PEGAWAI DI UPTD PUSKESMAS MAZO KABUPATEN NIAS SELATAN - Laia, Lifertina (Jurnal Ilmiah Mahasiswa Nias Selatan, 2025)
The purpose of this study was to determine the effect of work facilities on employee performance at UPTD Mazo Health Center, South Nias Regency. The type of research is the quantitative type. This type of research data is a type of primary data, namely data obtained directly from respondents. The source of data for this study was from employees using questionnaires, with the population and sample in this study being 39 respondents. The data analysis method used is a simple regression analysis with a value of Y = 14.505 + 0.655X. Based on the results of the hypothesis testing study with a calculated value of 4,997>ttable 1,687, the researcher concluded that there was a positive and significant influence between work facilities on employee performance at UPTD Mazo Health Center, South Nias Regency. The suggestions of this study are (1) To carry out a good job at UPTD Mazo Health Center, South Nias Regency, work facilities such as patient registration rooms, laboratories where hands are equipped are needed. (2) In improving employee performance, organizational leaders need to provide work facilities and create a work environment to maintain harmonious communication between colleagues.